Augustine’s Cassiciacum Dialogues - Heffernan, George 19XX- (Vigiliae Christianae, 2023)
These four volumes present Michael Foley’s comprehensive new edition of Augustine’s four Cassiciacum Dialogues: Against the Academics, On the Happy Life, On Order, and Soliloquies. Foley’s novel approach is unitary as well as unique insofar as it presents fluent translations of all the dialogues and includes detailed annotations, extensive commentaries, and numerous cross references, all of which are motivated by the intention to make Augustine’s earliest writings available to scholars and accessible to students in a single set of four books. Distinguished by philosophical astuteness, pedagogical insightfulness, and philological judiciousness, the entire edition represents a significant advancement of the study of Augustine, especially of the thought of the relatively neglected and undervalued early Augustine. It has the potential to become the standard edition of Augustine’s Cassiciacum Dialogues in English.